Pengadaan Tanah Untuk Kepentingan Umum Dalam Kegiatan Usaha Hulu Minyak dan Gas Bumi Proyek Jambaran Tiung Biru di Kabupaten Bojonegoro - Rizkyta Hamdany Jelmara (Lentera Hukum, 2016)
One of the development efforts within the national development framework organized by the Government is development for the Public Interest. Development for the Public Interest requires land as a means. Among the activities categorized in the public interest in Act No. 2 of 2012 are upstream oil and gas business activities. Oil and Gas is a non-renewable strategic natural resource controlled by the state and is a vital commodity that plays an important role in the supply of industrial raw materials, meeting energy needs in the country, and as a foreign exchange earner. In all developments involving upstream oil and gas business activities, especially in the land area, land can not be separated from the ingredients, one of which is land acquisition in the Jambaran Tiung Biru project located in Bojonegoro Regency. Based on Act No. 2 of 2012 and the implementing regulations of Presidential Regulation No. 71 of 2012, land acquisition starts from the planning, preparation, implementation, and delivery stages. For the acquisition of Perhutani land, it uses a loan to use the forest area and for the village treasury by swapping. Furthermore, a form of legal action can be taken as a result of the land acquisition of the Jambaran Tiung Biru project in Bojonegoro District, namely, firstly, a state administrative dispute through a claim to the State Administrative Court, while civil disputes through an objection to the District Court. KEYWORDS: Acquisitions of Land, Public Interest, Upstream Activities, Oil and Gas.